The influence of the level of physical activity and human development in the quality of life in survivors of stroke - Aidar, Felipe José; de Oliveira, Ricardo Jacó; Silva, António J.; de Matos, Dihogo Gama; Carneiro, André L.; Garrido, Nuno; Hickner, Robert C.; Reis, Victor M. (My University, 2011)
Background The association between physical activity and quality of life in stroke survivors has not been analyzed within a framework related to the human development index. This study aimed to identify differences in physical activity level and in the quality of life of stroke survivors in two cities differing in economic aspects of the human development index. Methods Two groups of subjects who had suffered a stroke at least a year prior to testing and showed hemiplegia or hemiparesis were studied: a group from Belo Horizonte (BH) with 48 people (51.5 ± 8.7 years) and one from Montes Claros (MC) with 29 subjects (55.4 ± 8.1 years). Subsequently, regardless of location, the groups were divided into Active and Insufficiently Active so their difference in terms of quality of life could be analyzed. Results There were no significant differences between BH and MCG when it came to four dimensions of physical health that were evaluated (physical functioning, physical aspect, pain and health status) or in the following four dimensions of mental health status (vitality, social aspect, emotional aspect and mental health). However, significantly higher mean values were found in Active when compared with Insufficiently Active individuals in various measures of physical health (physical functioning 56.2 ± 4.4 vs. 47.4 ± 6.9; physical aspect 66.5 ± 6.5 vs. 59.1 ± 6.7; pain 55.9 ± 6.2 vs. 47.7 ± 6.0; health status 67.2 ± 4.2 vs. 56.6 ± 7.8) (arbitrary units), and mental health (vitality 60.9 ± 6.8 vs. 54.1 ± 7.2; social aspect 60.4 ± 7.1 vs. 54.2 ± 7.4; emotional aspect 64.0 ± 5.5 vs. 58.1 ± 6.9; mental health status 66.2 ± 5.5 vs. 58.4 ± 7.5) (arbitrary units). Conclusions Despite the difference between the cities concerning HDI values, no significant differences in quality of life were found between BH and MCG. However, the Active group showed significantly better results, confirming the importance of active lifestyle to enhance quality of life in stroke survivors.
Keywords: Cerebrovascular Accident; Physical Activity; Stroke; Quality of Life